Low Serum 25-Hydroxyvitamin D Levels Are Associated With Hyperandrogenemia in Polycystic Ovary Syndrome: A Cross-Sectional Study - Shan, Chang; Zhu, Yu-chen; Yu, Jie; Zhang, Yi; Wang, Yu-ying; Lu, Nan; Cai, Jie; Liu, Wei; Tao, Tao (Frontiers in Endocrinology, 2022)
Background: Increasing evidence suggests a link between vitamin D and polycystic ovary syndrome (PCOS). However, whether vitamin D is related to hyperandrogenemia in PCOS is still inconclusive. The aim of our study is to elucidate the relationship between vitamin D and hyperandrogenemia in women with PCOS in China. Methods: This is a cross-sectional study including 625 Chinese women with PCOS and 217 controls from January 2016 to June 2020. The anthropometric and biochemical parameters related to 25(OH)D, sex steroids, glucose and lipid profiles were measured. Results: Serum 25(OH)D levels were lower in women with PCOS than controls (33.99 ± 15.05 vs 36.58 ± 16.49 nmol/L, P = 0.034), especially lower in hyperandrogenic women with PCOS (32.79 ± 14.24 vs 36.21 ± 16.27 nmol/L, P = 0.007). Higher 25(OH)D levels were independently associated with lower risks of hyperandrogenemia after adjusting demographic, metabolic and hormonal confounders (OR = 0.982, 95% CI: 0.969 - 0.995, P = 0.006). Consistent results were observed in subgroup analyses. Among PCOS women with vitamin D deficiency, females with age ≥ 26 years had lower risks of hyperandrogenemia (OR = 0.611, 95% CI = 0.389 - 0.958, P = 0.032), while overweight patients had higher risks of hyperandrogenemia (OR = 2.202, 95% CI = 1.130 - 4.293, P = 0.020) after adjusting multiple confounders. Conclusions: Our study reported lower vitamin D levels in Chinese women with PCOS, especially in those with hyperandrogenemia. An independent negative correlation between 25(OH)D and hyperandrogenemia was noted in PCOS. For PCOS women with vitamin D deficiency, females that have higher BMI with age < 26 years may be prioritized for hyperandrogenemia assessment.